2007
DOI: 10.1111/j.1742-4658.2007.06001.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhibitors of phosphodiesterase 1C on a human cellular system

Abstract: Different inhibitors of the Ca 2+ ⁄ calmodulin-stimulated phosphodiester-ase 1 family have been described and used for the examination of phospho-diesterase 1 in cellular, organ or animal models. However, the inhibitors described differ in potency and selectivity for the different phosphodiester-ase family enzymes, and in part exhibit additional pharmacodynamic actions. In this study, we demonstrate that phosphodiesterase 1C is expressed in the human glioblastoma cell line A172 with regard to mRNA, protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…We therefore confirmed the presence of PDE1 activity by measuring cGMP hydrolysis in the presence and absence of calcium and calmodulin in the whole BAT extract. This hydrolytic activity was increased by 2.7-fold by calcium and was fully inhibited by 100 nM SCH51866, a relatively selective PDE1 inhibitor (IC 50 for PDE1A, 10 nM) (Dunkern and Hatzelmann, 2007) (Fig. 2A).…”
Section: Pde Expression In Mouse Brown Adipocyte Modelsmentioning
confidence: 98%
“…We therefore confirmed the presence of PDE1 activity by measuring cGMP hydrolysis in the presence and absence of calcium and calmodulin in the whole BAT extract. This hydrolytic activity was increased by 2.7-fold by calcium and was fully inhibited by 100 nM SCH51866, a relatively selective PDE1 inhibitor (IC 50 for PDE1A, 10 nM) (Dunkern and Hatzelmann, 2007) (Fig. 2A).…”
Section: Pde Expression In Mouse Brown Adipocyte Modelsmentioning
confidence: 98%
“…S6B). Finally, it has been recently reported that vinpocetine may inhibit PDE-4 activity in vitro (26). Because PDE-4 is a well-known antiinflammatory target (27), we analyzed the ability of vinpocetine to inhibit PDE-4 by PDE assay.…”
Section: Vinpocetine Inhibits Monocyte Adhesion Of Huvecs and Chemotamentioning
confidence: 99%
“…The agent is widely used as a neuroprotective drug in the prevention and treatment of cerebrovascular diseases (Bereczki and Fekete, 2000;Nagy and Simon, 2004;Onishchenko et al, 2008;Fehér et al, 2009). In addition to its widely studied neuroprotective effects (Bönöczk et al, 2000;Tárnok et al, 2008;Nyakas et al, 2009) it is a well known phospho-diesterase (PDE) inhibitor (Dunkern and Hatzelmann, 2007;Deshmuk et al, 2009;Wunder et al, 2009) and voltage dependent sodium channel inhibitor (Ádám-Vizi, 2000). Most recently Jeon et al (2010) reported that vinpocetine is a potent antiinflammatory agent by targeting an IκB-related Kinases (IKK) dependent mechanism (cfr.…”
Section: Introductionmentioning
confidence: 98%